The 2nd International conference on prevention & management of chronic conditions - Mohamed, Che Rabiaah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
This study explored the educational needs of home-based stroke patients and family caregivers in the Kelantan state located at the northern part of the Malaysia Peninsular. This study used a qualitative approach guided by a theoretical framework, "Stroke Care Community Model" developed for this research. This study was in two phases. Phase 1 involved semistructured interviews with stroke patients, family caregivers and key members from health professionals. Phase 1 established the educational activities currently received and needed by patients and families. Phase 2 involved presenting the findings from Phase 1 to the previously interviewed health professionals through focus groups and individual interviews with the aim of establishing priorities and processes to develop education strategies for home-based stroke patients and their families. The fmdings revealed that the provision of information and education does not meet the needs of many patients and families. The educational needs are on a wide range of topics on stroke and stroke care. The findings also revealed some needs are religiously and culturally bound around prayer and traditional healthcare practice such as traditional massage. Therefore, there is a need to take the knowledge of what makes a difference to health outcomes of patients and families in a western context and work with this, utilising what is important in the culture of people at a local level. The next step to progress addressing educational needs requires a structured approach involving the formation of a multidisciplinary stroke team that incorporates cultural and religious practice.